2020
DOI: 10.21203/rs.3.rs-39673/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Novel Concepts in Cervical Cancer Screening. A Comparison of VIA, HPV DNA Test and p16ink4a/Ki-67 Dual-Stain Cytology in Western Kenya.

Abstract: Abstract Background: Screening of unvaccinated women remains essential to mitigate the high morbidity/mortality of cervical cancer. Here, we compared visual inspection with acetic acid (VIA), recommended by WHO as the most cost-effective screening approach in LMICs, with HPV-based screening, and usage of p16INK4a/Ki-67 dual stain cytology.Methods: We prospectively enrolled wome… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…In addition, an observational study showed that HIV‐infected individuals had a reduced rate of HPV clearance compared to non‐HIV ones 18 . This may be attributable to the common transmission mode of HPV and HIV, HPV persistence as a result of the inability to clear HPV infections, as well as reactivation of latent HPV infections 20 . Furthermore, from the cytological perspective, the numbers of Langerhans cells, CD4 + T lymphocytes, macrophages, neutrophils and natural killer cells are reduced in HIV‐infected patients, leading to the changes in local immunity and thus modulating HPV infection at the tissue level 21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, an observational study showed that HIV‐infected individuals had a reduced rate of HPV clearance compared to non‐HIV ones 18 . This may be attributable to the common transmission mode of HPV and HIV, HPV persistence as a result of the inability to clear HPV infections, as well as reactivation of latent HPV infections 20 . Furthermore, from the cytological perspective, the numbers of Langerhans cells, CD4 + T lymphocytes, macrophages, neutrophils and natural killer cells are reduced in HIV‐infected patients, leading to the changes in local immunity and thus modulating HPV infection at the tissue level 21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…Glandular involvement is closely related to HSIL] and its glandular extension is frequently associated with HSIL and requires further follow-up [30]. As screening for cervical cancer moves to primary ar-HPV testing, finding an effective classification and treatment for HPV + women is critical [10]. Risk thresholds guide whether a woman should return to routine screening or be referred for repeat testing, colposcopy, or immediate treatment [12,37]; provides long-term risk stratification compared to 5-year Pap triage; the risk of HSIL in HPV + / negative women and dual-staining cytology p15 / ki-67 is identical to the risk at 3 years in HPV + women and Pap negative at 1 year and is safely extended to 3-year intervals in these women [42].…”
Section: Discussionmentioning
confidence: 99%
“…Significance (ASC-US) diagnosed as mild or borderline lesions may progress to grade 2 or more severe Cervical Intraepithelial Neoplasia (CIN-2 +); the low specificity of HPV-ar tests, many women are referred for colposcopy, especially those under 30 years of age due to the higher prevalence of HPV infection; the prevalence of HPV-ar varies from 80 to 85% in LSIL, where they are sent for colposcopy or followed with Pap; women with HPVar, primary, positive for HPV-16 or HPV-18 are sent for colposcopy and for the other 12 HPV-ar, positive, they are followed up with Pap tests; if it is negative, the 12-month follow-up is recommended [10,11]; many ar-HPV-positive women need repeat Pap follow-up due to their low sensitivity; makes effective biomarkers required to classify ar-HPV-positive or normal Pap-16/18-negative women and identify women with HSIL on ASC-US / LSIL Pap. Evidence suggests that p16 / Ki-67 dual staining cytology is an alternative biomarker, with high sensitivity and general specificity for identifying HSIL [12][13][14][15][16].…”
Section: Patients With Pap Low-grade Squamous Intraepithelial Lesion (Lsil) and Cervical Atypical Squamous Cells Of Undeterminedmentioning
confidence: 99%
“…A secondary triage test of HPV-positive WLWH can be included to increase specificity but at the price of reducing sensitivity for high-grade cervical abnormalities as well as increasing cost, complexity, and burden on the health care system. Studies have evaluated visual triage (VIA or visual inspection with Lugol iodine), 181,184,187,209,210 cytology, 187,210,211 p16/Ki-67 dual-stain immunocytochemistry, 209 HPV genotyping/type restriction, 181,187,210,211,212,213 changing the positive cutoff point/viral load, 213 and host 214,215 and viral methylation 216 biomarkers measured from the cervical specimen. There is no consensus approach to choosing which triage test to use for HPV-positive WLWH, and the choice may depend on local capacities and which HPV test is being used for primary screening.…”
Section: Primary Prevention: Prophylactic Hpv Vaccinationmentioning
confidence: 99%